Internal Evaluation of Residency Training Programs for Selected Specialized Groups at Guilan University of Medical Sciences: The Essential Need for Monitoring Specialized Training Courses - Jalal Kheirkhah; Mirsaeed Attarchi; Abtin Heidarzadeh; Azim Mirzazadeh; Negar Pourvakhshoori; Ideh Dadgaran (Pizhūhish dar Āmūzish-i ̒ulūm-i Pizishkī)
In the medical education environment, ensuring and continuously improving quality has become an indispensable necessity. This technical note examines the internal evaluation process of residency training programs at the school of medicine of Guilan University of Medical Sciences in 14 steps. The primary objective of this study is to identify strengths and weaknesses in these educational programs and to provide actionable recommendations for enhancing educational quality. The findings of this evaluation can serve as a foundation for improving both processes and policies at the level of specialty groups and the university as a whole.